2020
DOI: 10.1029/2019wr026103
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Pseudomonas aeruginosa in Porous Media Mediated by Low‐Concentration Surfactants: The Critical Role of Surfactant to Change Cell Surface Hydrophobicity

Abstract: Transport of P. aeruginosa ATCC 9027 in quartz sands mediated by low‐concentration surfactants of sodium dodecyl benzene sulfonate (SDBS) or Triton X‐100 was investigated with column experiments. P. aeruginosa ATCC 9027 was cultured with glucose and hexadecane to produce cells with different initial cell surface hydrophobicity (CSH). Transport behavior of cells was characterized by breakthrough curves (BTCs) and deposition rate coefficients (kd) values were estimated by fitting the BTCs using colloid transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…The changes in calculated interaction energy due to variations in IS cannot explain the observed deposition pattern of D. discoideum spores but represent the breakthrough behavior of spores present in tap water, 39 particularly for biocolloids. 66,67 This analysis suggests that interfacial forces between spores and the quartz surface are significantly influenced by aquatic chemistry but may not be the main contributing factors regulating the deposition mechanisms of amoeba spores in porous media. Contributions from EPS, spore shape, localized heterogeneity, hydrophobicity, and negatively charged proteins, as well as the functional groups of EPS on the surface of amoeba spores, might also play important roles in the phenomena.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…The changes in calculated interaction energy due to variations in IS cannot explain the observed deposition pattern of D. discoideum spores but represent the breakthrough behavior of spores present in tap water, 39 particularly for biocolloids. 66,67 This analysis suggests that interfacial forces between spores and the quartz surface are significantly influenced by aquatic chemistry but may not be the main contributing factors regulating the deposition mechanisms of amoeba spores in porous media. Contributions from EPS, spore shape, localized heterogeneity, hydrophobicity, and negatively charged proteins, as well as the functional groups of EPS on the surface of amoeba spores, might also play important roles in the phenomena.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…Generally, for the same texture soil, the more porosity, the greater the permeability coefficient. Under the same hydraulic gradient, the groundwater flow velocity in the greater porosity soil would be greater, and therefore, the water infiltrated through the greater porosity soil would have a higher concentration of bacteria ( Smith et al, 1985 ; Huysman and Verstraete, 1993 ; Sepehrnia et al, 2019 ; Liu et al, 2020 ). In the present study, the lower TCC value samples were almost collected in the 0.5 porosity soils at 10°C, indicating that the soils with less porosity would retard the migration of coliforms, which could be observed at low temperature, while at high temperature, the retardation effect might be obscured by temperature effect.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, hydrophobicity is crucial in the early adsorption of germs to hydrophobic surfaces. The non-specific adsorption of germs on abiotic surfaces is favored by strong hydrophobic-ity [87], while hydrophilic viruses and bacteria exhibit greater migratory potential in aquifer media [88,89]. In a study of the colonization of microplastic surfaces by different bacteria in the presence of Tween-80, it was found that highly hydrophobic strains colonized the microplastic surfaces with significantly higher biomass [90].…”
Section: Hydrophobicitymentioning
confidence: 99%